2015
DOI: 10.1515/iral-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Processing Instruction on the acquisition of English simple past tense: Age and cognitive task demands

Abstract: The present study 1 investigates the effects of Processing Instruction on two different age groups and the role that cognitive task demands might play in the results generated by Processing Instruction. This study includes school-age children and adult native speakers of German learning English as a foreign language -a language combination not previously investigated within the Processing Instruction and individual differences research paradigm. The present study investigates directly whether two different age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…Since then, a large body of research on different grammatical structures in different languages has been conducted, including Spanish preterit (past) tense (Cadierno, 1995), Spanish accusative clitics (VanPatten, Farmer, & Clardy, 2009;VanPatten & Fernandez, 2004;VanPatten, Inclezan, et al, 2009;VanPatten & Sanz, 1995), Spanish subjunctive (Farley, 2001), Italian future tense (Benati, 2001), Spanish copula verbs ser and estar (Cheng, 2002), French causative (VanPatten & Wong, 2004), English simple past tense (Benati, 2005;Benati & Angelovska, 2015), English simple present tense (Bayrak & Soruç, 2017), and Japanese past tense and passive constructions (Benati, 2016). All these studies found similarly that on interpretation tasks, learners exposed to PI performed significantly better than those receiving the different types of PBI mentioned above.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…Since then, a large body of research on different grammatical structures in different languages has been conducted, including Spanish preterit (past) tense (Cadierno, 1995), Spanish accusative clitics (VanPatten, Farmer, & Clardy, 2009;VanPatten & Fernandez, 2004;VanPatten, Inclezan, et al, 2009;VanPatten & Sanz, 1995), Spanish subjunctive (Farley, 2001), Italian future tense (Benati, 2001), Spanish copula verbs ser and estar (Cheng, 2002), French causative (VanPatten & Wong, 2004), English simple past tense (Benati, 2005;Benati & Angelovska, 2015), English simple present tense (Bayrak & Soruç, 2017), and Japanese past tense and passive constructions (Benati, 2016). All these studies found similarly that on interpretation tasks, learners exposed to PI performed significantly better than those receiving the different types of PBI mentioned above.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…When researchers choose to apply explicit information in their PI treatment, however, it must contain information about the target form that learners are to learn along with the default mental strategies that they are likely to employ when processing the form (Benati & Angelovska, 2015). Also, it must be given prior to structured-input activities.…”
Section: Explicit Informationmentioning
confidence: 99%
“…The advice might include information like: in the sentence "The men made Richard buy some bread", the agent of the action "bought" should be assigned to 'Richard', not to 'the men'. To make the advice even clearer, researchers may provide further but brief explanation as to why it is Richard instead of the men who bought some bread (Benati & Angelovska, 2015).…”
Section: Explicit Informationmentioning
confidence: 99%
See 2 more Smart Citations